Fostering Sustainable Mangrove Ecotourism: A Collaborative Governance Approach on Bintan Island, Indonesia - Alfiandri, Alfiandri; Prasojo, Eko; Malik, Jalaluddin Abdul (Jurnal Studi Pemerintahan, 2024)
This study aims to identify deficiencies in the indicators and variables used to measure Collaborative Governance in the specific context of Mangrove-based ecotourism on Bintan Island, Riau Islands, Indonesia. Furthermore, this study explores the intricacies of Collaborative Governance circumstances to uncover the interactions between stakeholders as they synchronize their endeavors for development by specific visions and goals. This study utilizes a qualitative research methodology, incorporating primary data obtained through interviews and secondary data collected through transcripts. A comprehensive interpretative framework is developed using rigorous triangulation methods and NVivo software. The results highlight the ability of stakeholders to utilize Mangrove conservation regulations on Bintan Island to influence the development of Collaborative Governance models that incorporate both grassroots and top-level approaches. NVivo coding in this study identifies indicators and variables that may be considered weak, specifically within the context of the priority Penta Helix model. However, the study argues for a viable integration model incorporating Penta Helix indications. The present concept under consideration exhibits readiness for execution, enabling stakeholders to provide a wide range of offerings for Mangrove Ecotourism, catering to both domestic and foreign tourists.